PENGARUH PENAMBAHAN ARANG AKTIF TULANG IKAN DALAM PAKAN TERHADAP HISTOLOGI USUS IKAN NILA (Oreochromis niloticus) - Fanni Risna; Lia Handayani; Nurhayati Nurhayati (Jurnal TILAPIA, 2020)
This study aims to determine the effect of the addition of reactive activated charcoal to the intestinal histology of tilapia (Oreochromis niloticus). 8.5 Lampoh Keude, Aceh Besar. Measurement of intestinal histology of tilapia was carried out at the Histology Laboratory of the Faculty of Veterinary Medicine, Syiah Kuala University. The method used in this study is a completely randomized design method (CRD) with 4 treatments and 3 repetitions. The parameter tested was intestinal villi length. The treatments in this study were treatment A (control), treatment B (addition of activated charcoal 1%), treatment C (addition of activated charcoal 2%), and treatment D (addition of activated charcoal 3%). The results showed that the addition of the best charcoal active bone fish to intestinal histology was in treatment C with the addition of 2% activated charcoal with 344.44 µm intestinal villi length